A participação cidadã no Conselho Municipal (2015-2016) e sua contribuição para gestão da Política de Assistência Social de Feira de Santana-BA - Paiva, Eduardo Antonio Pedreira (2017)
Question Of The AmpliedState , Civil Society : one of the classiques about brazilian reality . The Relations Of Power Between Interests And Disputes .In sequel Brief Track Records Of Public Policy In Social Assistance In Brazil ,Structure And Runnings Of Manager Counsil Of Social Assistance And Participation Pedagogy . The methodology taken in question has followed the field of descriptive nature and qualifying aproach , since the main public were participating the city council of social assistance meetings and to them were aplied semi structured interviews and assistematic observation , considerating the ethical principles that normalizes researches envolving human beings . For the analysis and discussion of the results the technique of contents analysis has been used , that will enable the apprehension of the meaning that the participants of the city counsil of social assistance tributes to what they see and/or do about the city counsil of public assistance politics management .Finally the secundary data assemblance was realized through a documental and biographical cashback. Finally, it was verified that the contribution of the citizen participation in the municipal council in the management of the assistance policy is characterized by actions directed to the improvement and emptied of force for transformation.